PENGARUH KARAKTERISTIK KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DALAM BIDANG PERTANIAN DI KABUPATEN SLEMAN YOGYAKARTA - Fermana, Reza Eka; Sudrajat, Ign Suprih; Mawardi, Nanang Kusuma (JURNAL ILMIAH AGRITAS, 2025)
This study aims to determine how the influence of entrepreneurial characteristics on the success of Micro, Small and Medium Enterprises (MSMEs) in Sleman district in agriculture. The location of this research was carried out in Sleman district with two kapanewon, namely kapanewon Kalasan and kapanewon Tempel, which have the largest population of micro, small and medium enterprises (MSMEs) in agriculture. This research uses an approach with quantitative analysis, sampling by non probability sampling with accidental sampling method as many as 100 respondents. The data in this study used primary data and secondary data. The results obtained from this study prove that the business success variable is influenced by the entrepreneurial characteristics variable with indicators of self-confidence, risk-taking, commitment, work ethic and independent attitude.